A knowledge-based framework for integration of computer aided styling and computer aided engineering. Issue 4 (3rd July 2016) - Stadler, Severin; Hirz, Mario
ABSTRACT: The collaboration of industrial design and engineering design traditionally represents a potential area of conflict. In view of virtual product development, industrial styling-technology processes provide significant gaps on the way from industrial to engineering design. The present paper introduces a novel knowledge-based engineering framework for an effective and efficient integration of virtual styling and engineering disciplines including management of data quality, data structuring and meta-information of Class-A data. As a key aspect of the research work, Class-A verification configurations for implemented checks were developed and applied to the framework. The paper closes with an exemplary application of the framework on a typical automotive styling integration workflow including a short exemplary description of the developed software prototype. GRAPHICAL ABSTRACT: